Rural Sport Spectacles: Ice Hockey, Mythologies, and Meaning-Making in Rural Canada. (2nd November 2021) - Rich, Kyle A.
Abstract: Hockey occupies a prominent role in the folklore of rural Canada. In this paper, I discuss the role of hockey events in expressions of place-based rural cultures. I draw from fieldwork conducted in three separate communities to discuss the semiotic processes involved in these events and their relationship to myths of rurality. Informed by mythologies and the carnivalesque, I unpack the way these events are engaged in the social processes of their communities. Firstly, I discuss how athleticism and social structures are subverted and reconceptualized. Secondly, I explore the freedom, profanation, and collective laughter of these events. Cumulatively, this analysis explores how normalized, performative transgressions of sport and social norms may be implicated in the construction of myths of rurality. While these events provide a glimpse into the resiliency and creativity of rural people, they may also distract us from thinking critically about the social political contexts shaping rural life.